Communicating the Vision: How Face‐to‐Face Dialogue Facilitates Transformational Leadership. (21st February 2018) - Jensen, Ulrich Thy; Moynihan, Donald P.; Salomonsen, Heidi Houlberg
Abstract: For public managers facing political and structural constraints, transformational leadership promises to meaningfully improve outcomes by communicating an inspiring vision of the organization. But this promise rests to a great degree on the communication skills and behaviors of the leader. A better understanding of how transformational leadership functions in organizations therefore requires a deeper application of theory from the field of communications. This article explores the question of what communication behaviors facilitate transformational leadership. A media richness framework is applied to propose that transformational leaders will be most effective when employing a face‐to‐face dialogue approach to communication. Using a multisource longitudinal research design, the authors find support for this proposition in an empirical test of 256 Danish tax units, lower and upper secondary schools, child care centers, and bank branches. The findings also show that size matters, with diminishing effectiveness of face‐to‐face dialogue in larger organizations .